Denaturation and Renaturation of Viral Ribonucleic Acid I. Annealing R17 Ribonucleic Acid with Denatured Replicative Form or with Denatured Replicative Intermediate - Iglewski, Wallace J. (1967)
Purified replicative form (RF) and replicative intermediate (RI) prepared from Escherichia coli infected with R17 were denatured in 0.15 m NaCl, 0.015 m sodium citrate containing 65% dimethylsulfoxide. Denaturation of RF or RI was demonstrated spectrophotometrically, chromatographically, and by sedimentation analysis. Denatured RF or RI was annealed by carefully decreasing the temperature from 62 to 20 C. Annealing was accompanied by a decreased absorbance at 260 mμ. The decrease in absorbance during annealing appeared to be dependent upon the rate of cooling and the concentration of ribonucleic acid (RNA). Denatured RF or RI was annealed with R17 RNA which was labeled with (3)H-uridine. The annealed product was 73 to 82% resistant to 0.1 μg/ml of ribonuclease. Annealing R17 RNA with either denatured RF or RI resulted in the formation of a ribonuclease-resistant product with a sedimentation profile resembling that of native RI. Melting the annealed products in 85.7% dimethyl sulfoxide produced 27S single-stranded R17 RNA and a heterogeneous population of more slowly sedimenting RNA.